A new online tool to detect color misconceptions. Issue 3 (6th January 2016) - Naranjo Correa, Francisco Luis; Martinez Borreguero, Guadalupe; Perez Rodriguez, Angel Luis; Suero Lopez, Maria Isabel; Pardo Fernandez, Pedro J.
Abstract: In this work, we present an online test designed to ascertain what type of misconceptions people may have about color perception. It is noteworthy that only 15.7% of the over 20, 000 respondents answered correctly, and that the vast majority (78.2%) of incorrect response patterns on our test matched to just four sequences, corresponding with four types of misconceptions. © 2016 Wiley Periodicals, Inc. Col Res Appl 41, 325–329, 2016